The impact of life events on later life: a latent class analysis of the English Longitudinal Study of Ageing. (11th March 2020) - Enwo, O O; Player, E; Steel, N; Ford, J A
ABSTRACT: Background: Inequalities in life events can lead to inequalities in older age. This research aimed to explore associations between life events reported by older people and quality of life (QoL) and functional ability. Methods: Participants were grouped according to eight life events: parental closeness, educational opportunities in childhood, financial hardship, loss of an unborn child, bereavement due to war, involvement in conflict, violence and experiencing a natural disaster. Linear and logistic regressions were used to explore associations between these groups and the main outcomes of functional ability and QoL. Results: 7555 participants were allocated to four LCA groups: 'few life events' ( n  = 6, 250), 'emotionally cold mother' ( n  = 724), 'violence in combat' ( n  = 274) and 'many life events' ( n  = 307). Reduced QoL was reported in the 'many life events' (coefficient − 5.33, 95%CI −6.61 to −4.05), 'emotionally cold mother' (−1.89, −2.62 to 1.15) and 'violence in combat' (−1.95, −3.08 to −0.82) groups, compared to the 'few life events' group. The 'many life events' group also reported more difficulty with activities of daily living. Conclusions: Policies aimed at reducing inequalities in older age should consider events across the life course.